Factors Related to the Quality of Life among Elderly with Dementia: A Scoping Review - Anggraini Dwi Kurnia; Adit Krisnanda; Nur Lailatul Masruroh; Nur Melizza (Universitas Aisyah Pringsewu, 2023)
Dementia is a degenerative neurological condition in the elderly with a syndrome of decreased brain function that affects cognitive, memory and function. One of the significant impacts of dementia is that it causes changes in the quality of life influenced by various factors. This study aims to examine the factors that affect the quality of life of the elderly with dementia based on a scoping review. The design of this research is a literature review. Journal searches were performed on the NCBI, SpringerLink, BioMed Central and EBSCOhost websites using the keywords (“Factors”) OR (“Risk Factors”) OR (“Predictors”) AND (“Influence”) OR (Affect) OR (Impact) OR ( “Associated”) AND (“Quality of Life)” OR (Health Related Quality of Life”) AND (“Elderly”) OR (“Aged” OR (“Older Adults”) AND (“Dementia”) according to inclusion criteria. The journals were then assessed for quality using JBI (Joanna Briggs Institute) and analyzed using thematic analysis method. A total of 11 relevant journals were used in this study with the results of the analysis showing that physical factors are the biggest factors affecting the quality of life of elderly dementia by 46%, followed by psychological factors 34%, other factors 8%, demographic characteristics factors 8% and social factors 4 %. Based on the findings of this study, various treatment strategies or interventions should be developed and implemented to improve the quality of life of the elderly with dementia by further identifying the factors that affect the quality of life.